Hull Design Optimization and Ship Resistance Reduction: The Mediating Role of Hydrodynamic Performance and the Moderating Effect of Ship Speed ​​Variation - Wawan Kusdiana; Ardiansyah; Cahya Kusuma; Anton Nugroho; Jajang Amir Hidayat (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose –This study investigates the relationships among Hull Design Optimization (HDO), Hydrodynamic Performance (HP), Ship Resistance Reduction (SRR), and Ship Speed Variation (SSV) within an integrated mediation–moderation framework. Specifically, the study examines the direct effects of hull design optimization on hydrodynamic performance and ship resistance reduction, the mediating role of hydrodynamic performance, and the moderating effect of ship speed variation. Design/methods/approach – A quantitative explanatory research design was employed using a survey of 180 maritime professionals, including naval architects, shipyard engineers, hydrodynamic researchers, ship surveyors, consultants, lecturers, and graduate students. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings – The results indicate that Hull Design Optimization has a significant positive effect on Hydrodynamic Performance (β = 0.910, p < 0.001) and Ship Resistance Reduction (β = 0.445, p < 0.001). Hydrodynamic Performance significantly influences Ship Resistance Reduction (β = 0.347, p = 0.001) and partially mediates the relationship between Hull Design Optimization and Ship Resistance Reduction (β = 0.316, p = 0.001). Furthermore, Ship Speed Variation significantly moderates the relationship between Hydrodynamic Performance and Ship Resistance Reduction (β = 0.135, p < 0.001). The structural model demonstrates substantial explanatory and predictive power. Research implications/limitations – The findings emphasize the importance of integrating hydrodynamic considerations and operational speed conditions into ship design optimization strategies. However, the study relies on expert perceptions and a cross-sectional survey design, which may limit the generalizability of the findings to actual vessel operations. Originality/value – This study contributes to the maritime engineering literature by integrating mediation and moderation mechanisms within a single SEM-PLS framework, providing a more comprehensive explanation of how hull optimization influences ship resistance reduction through hydrodynamic performance under varying operational speed conditions.